Faktor-Faktor yang Mempengaruhi Pendapatan UMKM Di Kota Padang - Annisa Nurfathira; Zahara Zahara; Dita Maretha Rissi; Wiwik Andriani (Akuntansi dan Manajemen, 2026)
This research aims to identify and analyze the factors that effect income of Micro, Small, and Medium Enterprises (MSME) in Padang City. The analyzed factors are e-commerce usage, product innovation, business capital, business duration, and labor. The research applied a quantitative descriptive method with a sample of 105 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed through multiple linear regression with SPSS version 26. The findings reveal that e-commerce, business capital, and labor have a positive and significant effect on Micro, Small, and Medium Enterprises income, while product innovation and business duration do not show significant effects on its. The simultaneous test indicates that all five variables collectively have a significant influence on Micro, Small, and Medium Enterprises income in Padang City. These results conclude that the utilization of e-commerce technology, sufficient business capital, and labor availability are the main drivers of Micro, Small, and Medium Enterprises income growth, whereas product innovation and business duration have not yet made a meaningful contribution.